The Effect of Using Buzz Group Technique on Students Ability in Writing Analytical Exposition Paragraph - Nuardi Nuardi; M. Syafii S. M. Syafii S.; Inna Hayatul Anuar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The objectives of the research were to know students’ ability in writing analytical exposition paragraph taught by using buzz group and taught without using buzz group, to get information the significant effect of students’ ability in writing analytical exposition paragraphs by using buzz group. In this research, the research design was a quasi experimental research.The population of this research was the eleventh grade students of Private Senior High School YKPP Dumai. There werenine classes; the number of population was233 students.The researcher used cluster random sampling as the technique sampling of the research. Class XI IPA 1 was control class, while XI IPA 5 was experimental class.Based on the data analysis, the researcher concluded that the score of sig. is higher than α (0.05 > 0.000) in the other word, there is a significant effect of using Buzz Group Technique on students’ ability in writing analytical exposition paragraph of the eleventh grade students at Private Senior High School YKPP Dumai. It means that Ha was accepted and Ho was rejected.